2019
DOI: 10.1111/mms.12624
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral responses of satellite tracked Blainville's beaked whales (Mesoplodon densirostris) to mid‐frequency active sonar

Abstract: The vulnerability of beaked whales (Family: Ziphiidae) to intense sound exposure has led to interest in their behavioral responses to mid‐frequency active sonar (MFAS, 3–8 kHz). Here we present satellite‐transmitting tag movement and dive behavior records from Blainville's beaked whales (Mesoplodon densirostris) tagged in advance of naval sonar exercises at the Atlantic Undersea Test and Evaluation Center (AUTEC) in the Bahamas. This represents one of the largest samples of beaked whales individually tracked d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…Thus, this discrepancy remains unresolved. Generally, while recent efforts have engaged operational sources, many CEEs will continue to rely on weaker signals compared to real sonar sources, with potential implications for the characterisation of cetacean responses, but studies based on opportunistic exposures to real Navy activities could be useful ( Joyce et al, 2020 ). The continuous function for distance, on the other hand, predicted a relatively small footprint of each disturbance event because there were few experimental exposures beyond 5 km.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this discrepancy remains unresolved. Generally, while recent efforts have engaged operational sources, many CEEs will continue to rely on weaker signals compared to real sonar sources, with potential implications for the characterisation of cetacean responses, but studies based on opportunistic exposures to real Navy activities could be useful ( Joyce et al, 2020 ). The continuous function for distance, on the other hand, predicted a relatively small footprint of each disturbance event because there were few experimental exposures beyond 5 km.…”
Section: Discussionmentioning
confidence: 99%
“…Previous efforts in these areas suggested that there were also biological differences in fish and invertebrates in the upper water column between these 2 zones (Hazen et al 2011). Two additional, similarly sized zones were sampled in areas adjacent to the north and south of the active range, as these areas are likely used by animals as a refuge during navy sonar exercises (McCarthy et al 2011, Tyack et al 2011, Joyce et al 2019. Data from these 4 zones were compared with a region approximately 170 km north of the range, on the southwest of Great Abaco Island.…”
Section: Field Sitementioning
confidence: 99%
“…There is considerable evidence of atypical mass stranding events of these species associated with military sonar exercises (Cox et al 2006, Filadelfo et al 2009). Recent evidence suggests that in addition to relatively rare mortality events, beaked whales that inhabit naval training ranges experience frequent behavioral disturbances including reduced dive rates and spatial displacement from preferred habitats (McCarthy et al 2011, Joyce et al 2019). These behavioral changes likely have energetic and reproductive consequences which may lead to changes in population demographics (King et al 2015, Hin et al 2019.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of information on beaked whales is even more alarming given that they have been identified as sensitive to anthropogenic noise [25,31,32]. In particular, midfrequency military sonar exposure has been blamed in many atypical mass stranding events [33][34][35] and shown to induce behavioural changes [25,36,37]. Although much less studied, other intense sound sources such as shipping and seismic airguns are of concern [34,38,39].…”
Section: Introductionmentioning
confidence: 99%